Sequential Synthesis and Active‐Site Coordination Principle of Precious Metal Single‐Atom Catalysts for Oxygen Reduction Reaction and PEM Fuel Cells. Issue 20 (9th April 2020) - Liu, Qingtao; Li, Yongcheng; Zheng, Lirong; Shang, Jiaxiang; Liu, Xiaofang; Yu, Ronghai; Shui, Jianglan
Abstract: Carbon‐supported precious metal single‐atom catalysts (PM SACs) have shown promising application in proton exchange membrane fuel cells (PEMFCs). However, the coordination principle of the active site, consisting of one PM atom and several coordinating anions, is still unclear for PM SACs. Here, a sequential coordination method is developed to dope a large amount of PM atoms (Ir, Rh, Pt and Pd) into a zeolite imidazolate framework (ZIF), which are further pyrolyzed into nitrogen‐coordinated PM SACs. The PM loadings are as high as 1.2–4.5 wt%, achieving the highest PM loadings in ZIF‐derived SACs to date. In the acidic half‐cell, Ir1 ‐N/C and Rh1 ‐N/C exhibit much higher oxygen reduction reaction (ORR) activities than nanoparticle catalysts Ir/C and Rh/C. In the contrast, the activities of Pd1 ‐N/C and Pt1 ‐N/C are considerably lower than Pd/C and Pt/C. Density function theory (DFT) calculations reveal that the ORR activity of PM SAC depends on the match between the OH* adsorption on PM and the electronegativity of coordinating anions, and the stronger OH* adsorption is, the higher electronegativity is needed for the coordinating anions. PEMFC tests confirm the active‐site coordination principle and show the extremely high atomic efficiency of Ir1 ‐N/C. The revealed principle provides guidance for designing future PM SACs for PEMFCs. Abstract : A sequential coordination method is invented to dope a large quantity of precious metal (PM) into a zeolite imidazolate framework and synthesize high‐metal‐loaded Ir, Rh, Pd, and Pt single‐atom catalysts (SACs). The oxygen reduction reaction activity of PM SACs depends on the match between the electronegativity of the coordinating anions and the oxygen affinity of the PM.